Quality of Work Life of Women Employees in Private Sector Organizations in Ernakulam District of Kerala - Netto, Cecily Shibi (Prabandhan: Indian Journal of Management, 2018)
Private sector organizations provide huge employment opportunities to women, and women make remarkable contributions to various organizations in the private sectors of the economy. This study analyzed the quality of work life of women employees in private sector organizations on the basis of their demographic factors, and 96 women employees working in various private sector organizations located in Ernakulam district of Kerala were purposively selected in a descriptive cross-sectional survey. Harvard Professor Richard E. Walton’s eight-dimension scale was utilized to measure the quality of work life perception among women employees. Non-parametric tests such as Mann - Whitney U test, Kruskal - Wallis H test, and Pearsons’s correlation were used as the major data analysis tools in the present study. It was observed that a significant difference existed between marital status of the respondents for work and total life space; educational qualification for social relevance of work life; organization type for adequate and fair compensation, constitutionalism, and social relevance of work life; work experience for social integration in the work organization; and monthly income for adequate and fair compensation, opportunities to use and develop human capacities, opportunity for continued growth and security, and social relevance of work life. It was also revealed that there was a significant positive relationship between the overall quality of work life and the majority of each dimensions of QWL.